Differential Affinities of a Pocillopora damicornis Galectin to Five Genera of Symbiodiniaceae at Different Temperatures - Wang, Xingjuan; Wu, Zhongjie; Wu, Yibo; An, Mingxun; Zhou, Zhi; Lin, Senjie (Frontiers in Marine Science, 2021)
The symbiosis of coral-Symbiodiniaceae is the quintessential basis of the coral reef ecosystem, and its breakdown results in coral bleaching, one of the most severe ecological catastrophes in the ocean. Critical to the establishment of the symbiosis is the host’s specific recognition of the symbionts through the binding of the coral host’s pattern recognition receptors (PRRs) to the symbiont cell surface’s glycoconjugates. However, the molecular basis for this recognition process is poorly understood. The present study investigated the binding affinities of the coral galectin PdGLT-1 to different symbiodiniacean species under different temperatures. At 25°C, the PdGLT-1 recombinant protein (rPdGLT-1) exhibited different binding affinities to different symbiodiniacean species from five genera, with a significantly higher binding affinity (p < 0.05) to Fugacium kawagutii (2.6-fold) and Cladocopium goreaui (1.9-fold) than Symbiodinium microadriaticum. The binding topology of rPdGLT-1 differed among the five symbiodiniacean species; for S. microadriaticum, Breviolum minutum, and Durusdinium trenchii, the binding was on some specific sites on the cell surface, whereas for C. goreaui and F. kawagutii, the binding signals were detected over the whole cell surface. Interestingly, PdGLT-1 binding induced agglutination of F. kawagutii cells but not of C. goreaui, explaining why C. goreaui was the most dominant symbiodiniacean symbionts in corals. Moreover, the affinity of rPdGLT-1 to Symbiodiniaceae was affected by temperature, and the highest binding affinities were observed at 30, 20, 30, 35, and 30°C for S. microadriaticum, B. minutum, C. goreaui, D. trenchii, and F. kawagutii, respectively. The optimal binding temperatures were consistent with the current understanding that D. trenchii was the most thermal resistant among these species. These results suggest that the binding affinity of the PRR PdGLT-1 may determine the specificity of host-symbiont pairing and explain why Cladocopium is the dominant symbionts of coral P. damicornis at normal temperature, and corals with Durusdinium symbionts may survive better at high temperature.